The Efficacy of Insole on Pain, Function and Biomechanics in Individuals with Patellofemoral Pain Syndrome; A Review Article - Tahmoores Tahmasbi; Fatemeh Farazmand; Pegahalsadat Hosseini (Vesnu Publications, 2016)
Introduction: Patellofemoral pain syndrome (or anterior knee pain) is one of the most common musculoskeletal conditions in ‎sport medicine clinics and one of the most common interventions in management of this syndrome is foot insoles. ‎Despite the widespread use of foot orthoses, the efficacy of these interventions is controversial. Therefore, the aim ‎of this study was to review the papers about the efficacy of foot insole on pain, function and biomechanics in ‎individuals with patellofemoral pain syndrome.‎ Materials and Methods: A literature search was carried out in some data bases such as PubMed, Iranmedex, ScienceDirect, Medline, Magiran and ISI Web of ‎science between the years 2000 and 2015. The quality of the research studies was evaluated using Black and ‎Downs tool.‎ Results: After search in Persian and English databases, we found 117 papers. According to keywords and titles, 12 articles ‎were included in the final review.‎ Conclusion: Foot orthoses may improve pain and function in individuals with patellofemoral pain syndrome; although these ‎interventions are more effective in patients with foot pronation.‎